EPIDEMIOLOGY OF ACUTE PAIN SYNDROME IN OTORHYNOLARYNGOLOGY - I. V. Kastyro (Acta Biomedica Scientifica, 2012)
The article reviews epidemiology of acute pain syndrome in urgent and elective otorhynolaryngology. 161 patients with acute pain on the background of acute ENT diseases (group 1) and 130 patients immediately after routine surgery were questioned. Total values on the pain level of the patients of the group 1 showed that 27,32 % of patients had. mild pain, 30,43 % of patient had. medium pain, 31,05 % had. strong pain and. 11,18 % had. very strong pain. In the group 2 25,38 % of patients had low pain level, 40,76 % had medium pain level, 26,92 % had. highpain level and. 6,92 % had. very high pain level. Understanding of pain syndrome structure at different ENT disorders helps in choice of adequate analgetic therapy and prevents development of chronic pain syndrome.